Derma-like antibacterial polysaccharide gel dressings for wound care. (August 2022) - Xiong, Yan-Hua; Zhang, Lujiao; Xiu, Zongpeng; Yu, Bingran; Duan, Shun; Xu, Fu-Jian
Abstract: Large skin wound infections have high morbidity, which threaten the health of human beings severely. It is essential to develop new wound dressings that can block microbial invasion, eliminate bacteria effectively, adhere to wounds firmly, and have good biocompatibility. In this work, we designed a kind of polysaccharide gel (DLG) dressings with derma-like structure that had good wound care performances. With a facile penetration cross-linking method by the Schiff base reaction between oxidized hyaluronic acid solution and carboxymethyl chitosan solution with higher viscosity, a gradient porous structure was formed inside DLG to mimic the structure of derma, which was due to the simultaneous penetration and reaction processes between two viscous solutions. This derma-like structure endowed the gel dressings with the abilities of self-adhesion to wounds and barriers against bacteria. Through the introduction of cuttlefish juice and gentamycin, the modified gel dressings (DLG-GS) showed mild photothermal effects under the near infrared irradiation at the wavelength of 808 nm, which could reach and maintain the temperature of 45 °C. The mild heat could act together with gentamycin to produce a rapid bactericidal performance within 5 min. Meanwhile, the polysaccharide gel dressings had good biocompatibility. The in vivo anti-infection properties of DLG-GS was demonstrated by an animal model of infected full-thickness skin defect. This strategy provided a feasible solution for the prevention and treatment of infected large wounds. Statement of significance: Derma-like antibacterial gel dressings (DLG-GS) with high bacterial barrier ability, strong tissue adhesive property and good biocompatibility were constructed by a penetration cross-linking method. DLG-GS could eliminate bacterial infection within 5 min due to the rational combination of a mild photothermal effect and antibiotics. DLG-GS showed high anti-infection and wound healing properties in an animal model of infected full-thickness skin defect. This study provides a flexible and universal strategy for the development  of antibacterial wound dressings. Graphical abstract: Image, graphical abstract